The reliability and validity of the Malay version 17-item diabetes distress scale - Chew, Boon How; Mukhtar, Firdaus; Mohd Sidik, Sherina; Paimin, Fuziah; Hassan, Noor Hasliza; Jamaludin, Nor Kasmawati (Academy of Family Physicians of Malaysia, 2015)
Introduction Diabetes-related distress (DRD) refers to patient’s concerns about diabetes mellitus, its management, need of support, emotional burden and access to healthcare. The aim of this study was to translate and examine the psychometric properties of the Malay version of the 17-item Diabetes Distress Scale (MDDS-17) in adult patients with type 2 diabetes mellitus (T2D).